Prevalence of chlamydia in young adulthood and association with life course socioeconomic position: birth cohort study. - Joanna Crichton; Matthew Hickman; Rona Campbell; Jon Heron; Paddy Horner; John Macleod (PLoS ONE)
Background Few estimates are available of chlamydia prevalence in the general population. Existing studies have limited scope to explore potential selection bias or associations with socioeconomic position. Methods We examined the prevalence of Chlamydia trachomatis infection and associations with life-course socioeconomic position in the Avon Longitudinal Study of Parents and Children in England. Chlamydia infection was measured through nucleic acid amplification test of urine specimens. Results 4864 (51%) of those invited attended the clinic (mean age 17.8; SD 0.37 years). (60%) provided a urine specimen. Prevalence was 1.0% (95% CI 0.6 to 1.6) among participants reporting sexual activity. Risk of infection was strongly associated with life course social disadvantage and with recent sexual behaviour. After adjustment for other measures of disadvantage and for sexual behaviour the strongest risk factors for infection were lower maternal educational attainment (OR 9.1 (1.1, 76.7)) and lower participant educational attainment at age 11 (OR 5.0 (1.5, 16.5)). Both clinic attendance and agreement to test were lower amongst the disadvantaged. Adjustment for selective participation based on detailed information on non-participants approximately doubled prevalence estimates. Prevalence was higher in sexually active women (1.4% (0.7 to 2.4) than men (0.5% (0.1 to 1.3)). Conclusions Chlamydia prevalence in this general population sample was low even after adjustment for selective participation in testing. These estimates of prevalence and patterns of association with socioeconomic position may both reflect recent screening efforts. Prevalence was higher amongst the disadvantaged who were also less likely to engage in testing. Our results reveal the importance of monitoring and addressing inequalities in screening programme participation and outcomes.